Identification and Characterization of a New Porin Gene of Klebsiella pneumoniae: Its Role in β-Lactam Antibiotic Resistance - Doménech-Sánchez, Antonio (American Society for Microbiology, 1999)
Klebsiella pneumoniae porin genes were analyzed to detect mutations accounting for the porin deficiency observed in many β-lactam-resistant strains. PCR and Southern blot analysis revealed the existence of a third porin gene in addition to the OmpK36 and OmpK35 porin genes previously described. This new porin gene was designated ompK37 and is present in all of the clinical isolates tested. The OmpK37 porin gene was cloned, sequenced, and overexpressed in Escherichia coli. In contrast to that of the major porins, OmpK37 porin expression was only detectable by Western blot analysis in porin-deficient β-lactam-resistant strains, suggesting strong down regulation under standard laboratory conditions. Functional characterization suggested a narrower pore for the OmpK37 porin than for K. pneumoniae porins OmpK36 and OmpK35. This correlated with the susceptibility to certain β-lactam antibiotics, since a K. pneumoniae strain expressing porin OmpK37, but not porin OmpK36 or OmpK35, was less susceptible to β-lactam antibiotics than the same strain expressing either porin OmpK36 or OmpK35.